ARTIFICIAL INTELLIGENCE AS A FACTOR IN ENHANCING THE EFFECTIVENESS OF DISTANCE AND HYBRID LEARNING (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the impact of artificial intelligence on the effectiveness of distance and hybrid learning within educational institutions. It analyzes modern AI technologies and their application in personalizing the educational process, monitoring student progress, and boosting motivation. Particular attention is paid to teacher training, the ethical aspects of AI implementation, as well as the potential risks and controversies associated with technological dependency. Based on this analysis, recommendations are proposed for optimizing the use of AI in educational practice.